Perception of Parents with Low Education on the Continuity of Children’s Education in Indonesia - Abdul Khobir; Nur Daningsih; Muhammad Maskur Musa (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the perception of parents with low education on the continuity of their children’s education in Indonesia. This research method used field research with a qualitative approach. Data collection techniques used interviews, observation, and documentation. This research data analysis technique had 3 steps: data reduction, data presentation, and drawing conclusions. The study results explain that some parents had a bad view of their children’s education. However, many also had a positive opinion that parents would continue their children’s education to a higher level, at least until high school, following the wishes of the children themselves. Parents’ support that their children’s education was essential currently. This education can be a provision for children to have a better fate than their parents. Children attending school up to higher education can provide valuable experience, especially for children. With education, children can get an established and good job to fulfill their lives later.